Structural and functional insights into IZUMO1 recognition by JUNO in mammalian fertilization - Kazuki Kato (Nature Portfolio, 2016)
Sperm-egg fusion requires the interaction between IZUMO1 on the sperm and JUNO on the egg. Here, the authors report the crystal structure of mouse JUNO, and use it to explain its lack of binding to folate, along with in vivofunctional analyses.